PENGENDALIAN PROYEK DENGAN METODE EARNED VALUE ANALYSIS PEMBANGUNAN GEDUNG (Studi Kasus: Pembangunan Gedung Rumah Sakit Muhammadiyah Gresik tahap I) - Amalina, Shafira Dwi (Universitas Negeri Surabaya, 2023)
Controlling costs and time is the most important thing in the construction implementation process so that the project can be carried out according to the initial plan. The Earned Value Analysis method is one of the project control methods used in this research to determine the cost & time performance of the project and to determine the estimated cost & time required to complete the project. The data used in the research are S-Curve, RAB, progress reports, and actual project cost recapitulation. From this data, the values of the indicators used in Earned Value Analysis are obtained, the BCWS, BCWP, ACWP, CV, SV, CPI, SPI, ETC, EAC, ETS and EAS values. In accordance with the analysis that has been carried out, the project time performance results do not experience cost deviations and the achievement index is quite good, it is known from all results that the CV value is positive (+) and the CPI value is above 1 (>1). The project time performance obtained a final SV value of -1,396,389,988 (-) and an SPI value of 0.658 (<1), this indicates that time deviations occurred and the performance achievement index decreased. The estimated project completion cost (EAC) was obtained at a value of Rp 30,946,113,578, so there was a savings from the project plan cost of Rp 15,970,422. Then the estimated project completion time (EAS) is 58,565 weeks, so that the project is 14,565 weeks slower than the project plan time.